China-Africa relations: do non-economic drivers matter? - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2021)
This article examines the place of non-economic drivers in China-Africa relations. While existing studies are hinged on economic relations between Beijing and the continent, this study focuses on non-economic aspects that underlie Africa's relations with China. Taking the soft power approach, the paper illuminates on the salience of attractiveness in international politics and interrogates sources of China's attractiveness in the continent and compares China's actions with those of traditional actors for broader empirical coverage and methodological rigour. The authors argue that while economic drivers are an important basis for understanding China-Africa relations, several fundamental features beyond the economic relations supplement the growing relations between Beijing and Africa.
Keywords: China-Africa relations; non-economic drivers; soft power; attractiveness; NEO-COLONIALISM; POLITICS; DIPLOMACY; THREAT; RISE; WAR